Localising text and performance: avenues for exploring Shakespeare and cultural-creative adaptation - Ali Termizi, Arbaayah; Fretz, Claude; Georgopoulou, Xenia; Qingchen, Dong (Universiti Putra Malaysia, 2024)
The article comprises three case studies examining Shakespearean productions across varied geographical and methodological arenas, aiming to review and identify promising avenues for new directions in performance research. Through analyses of political adaptations in Greece, cultural hybridity in Malaysian productions, and practice-based research models (involving rehearsal studies) deployed at the Folger Theatre (USA), this article explores the mechanisms by which Shakespeare’s works blend into different historical, political, and cultural contexts. In doing so, it advocates for a departure from the conventional emphasis on textual or performative authenticity in Shakespeare studies. By documenting how diverse values, practices, and experiences shape creative processes, it reveals these endeavours as dynamic networks of cultural-creative collaboration. Ultimately, this study transcends traditional geographical and methodological limitations, urging readers to recognise and celebrate the ever-evolving presence of Shakespeare in diverse cultures and media.